Strategy For Islamic Religious Education Teachers in Growing Aqidah Towards Students in Batanghari, Lampung Timur - Fandi Asy'arie, Bima (Program Pascasarjana, UIN Alauddin Makassar, 2023)
This study aims to analyze (1) Strategies for planting creeds in students. (2) Know the factors that support and inhibit the cultivation of creed in students. This research is limited by place, as the object of study has been carried out at SMP Islam Qur'ani Batanghari, East Lampung. This type of research is Field Research, or called field research with qualitative analysis. Data collection methods through observation, interviews, and documentation. Data analysis techniques can be done through data education, presenting data, and drawing conclusions. The data acquisition in this study is teachers as examples, habituation, advice, supervision, conversations, stories, lectures, demonstrations, Targhib, and Tarhib. The overall strategy that PAI teachers have carried out has been running optimally, this aims to increase aqidah in students to be better.